Layer 4 of mouse neocortex differs in cell types and circuit organization between sensory areas - Federico Scala (Nature Portfolio, 2019)
Layer 4 of the mammalian neocortex is important for cortical information processing but its cellular composition and local circuits remains elusive. The authors compared two primary sensory cortical areas of mice and found differences in cell composition and local connectivity.